2005
DOI: 10.1111/j.1600-0463.2005.apm1130303.x
|View full text |Cite
|
Sign up to set email alerts
|

Complement activation in acute coronary syndromes

Abstract: The complement system is part of the host defence response. However, considerable evidence suggests that complement plays an important role in the pathophysiology of ischemic heart disease. The aim of this study was to evaluate complement activation in patients with all forms of acute coronary syndromes (ACS) and to examine the relationship between the degree of complement activation and myocardial injury. The study population included 152 subjects (26 females): 82 with ACS (35 acute myocardial infarction (AMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…(31) Association of the single nucleotide polymorphism (SNP) Y402H of the CFH gene with increased cardiovascular risk has been controversial. (32),(33),(34),(35) However, complement activation has been shown to be higher in individuals presenting with ACS,(36) and recently to be associated with an anti-coagulant role. (37) The biological activity of CFH binding to MDA-LDL decreased by ~12% post PCI, and there was an increase of ~6% at 3-7 days post PCI that remained until 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…(31) Association of the single nucleotide polymorphism (SNP) Y402H of the CFH gene with increased cardiovascular risk has been controversial. (32),(33),(34),(35) However, complement activation has been shown to be higher in individuals presenting with ACS,(36) and recently to be associated with an anti-coagulant role. (37) The biological activity of CFH binding to MDA-LDL decreased by ~12% post PCI, and there was an increase of ~6% at 3-7 days post PCI that remained until 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous report had reported that stepwise multiple regression analysis did not identify HDL-C as a significant determinant of C1q–APN [17]. Some studies reported that serum complement levels were markedly elevated in ACS compared with SAP patients, suggesting an acute phase and inflammatory response [31,32]. The protein family CTRPs (C1q/TNF-related proteins) has recently been identified as adiponectin paralogs and some CTRP members share adiponectin's metabolic regulatory function and regulate cardiac remodeling after acute myocardial infarction [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, plasma C3 and C4 levels in ACS showed a relationship with peak creatine kinase (CK)-MB and troponin I levels. The relationship of C3, C4 levels with peak CK-MB and troponin I levels further suggests that complement activation is related to necrosis within the myocardium 7. Lack of significance between some correlations may be due to the small sample size, which was a limitation of this study.…”
Section: Discussionmentioning
confidence: 86%